Victorian values: past and present in the refurbishment of London's historic churches. Issue 1 (2nd January 2023) - Jordan, Kate
ABSTRACT: In 1842, The Ecclesiologist, a publication dedicated to the development of church architecture, suggested that 'to restore is to revive the original appearance … lost by decay, accident, or ill-judged alteration.' This sentiment informed the restoration of countless medieval churches over the nineteenth century and ultimately triggered the foundation of the Society for the Protection of Ancient Buildings (SPAB); the body that would shape twentieth-century conservation philosophy. This article suggests that a number of recent church schemes in London illustrate a growing shift away from orthodox conservation principles towards creative restoration. Three Anglican churches that are currently undergoing a programme of refurbishment will be examined to shed light on emerging practices. Though none of the refurbishments have attempted to recreate the original church, all three have foregrounded the original shell and plan and, in doing so reflect The Ecclesiologist's position that 'we must, whether from existing evidences or from supposition, recover the original scheme of the edifice, as conceived by the first builder … ' This article explores the factors that are influencing new approaches in church refurbishments, reading these against nineteenth-century debates on conservation and restoration.